Sistem Informasi Manajemen Rumah Sakit Dalam Meningkatkan Efisiensi : Mini Literature Review - dr. Nadifa Maulani Fadilla (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Healthcare services are the main topic because of the high complexity challenges in the health sector. The purpose of this study is to determine the implementation of Hospital Information System (HIS) in increasing the efficency of healthcare services. The method used in this article is literature searches related to Hospital Information System. The writing arrangement based on the mind map that is structured to answer scientific questions according to the purpose of this article. The results showed that Hospital Information System can minimize the complexity of healthcare services by increasing organizational efficiency through innovation in developing information system based on business process management, service automation, reducing costs, improving hospital performance, which aims to develop human resources, organizational development, and technological quality improvement to achieve efficency in healthcare services.